2004
DOI: 10.1001/jama.292.7.828
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin E and Respiratory Tract Infections in Elderly Nursing Home Residents

Abstract: NFECTIONS, PARTICULARLY RESPIRAtory tract infections, are common in elderly individuals, resulting in decreased daily activity, prolonged recovery times, increased health care service use, and more frequent complications, including death. [1][2][3][4][5][6][7][8][9][10][11] In the United States, an estimated 43% of elderly persons will be admitted to a nursing home, with more than 85% of them admitted to long-term (Ͼ1 year) care facilities. 12 Infections occur more frequently in nursing home residents than amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
229
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 281 publications
(235 citation statements)
references
References 45 publications
1
229
1
4
Order By: Relevance
“…We have previously demonstrated a beneficial effect of vitamin E on T cell-mediated immune function in the aged, in both human clinical trials and in animal studies. The effects include improvement in delayed type hypersensitivity response, in vitro T cell proliferation, and IL-2 production (33)(34)(35) and improved resistance to respiratory infections (36,37). We further demonstrated that naive, but not memory, T cells from old mice displayed the greatest age-related defects, and were uniquely responsive to vitamin E supplementation, resulting in increased cell divisions and IL-2 production in response to TCRmediated stimulation in these cells (6).…”
mentioning
confidence: 73%
“…We have previously demonstrated a beneficial effect of vitamin E on T cell-mediated immune function in the aged, in both human clinical trials and in animal studies. The effects include improvement in delayed type hypersensitivity response, in vitro T cell proliferation, and IL-2 production (33)(34)(35) and improved resistance to respiratory infections (36,37). We further demonstrated that naive, but not memory, T cells from old mice displayed the greatest age-related defects, and were uniquely responsive to vitamin E supplementation, resulting in increased cell divisions and IL-2 production in response to TCRmediated stimulation in these cells (6).…”
mentioning
confidence: 73%
“…Flavonols along with other flavonoids and polyphenolic compounds influence the immune system and inflammatory cells (Middleton et al, 2000) and have antimicrobial properties (Conti et al, 1998;Middleton et al, 2000;Puupponen-Pimiä et al, 2001). The most convincing evidence on the efficacy of vitamins in CC treatment or prevention concerns people whose immune system may not function optimally or who are under exceptional stress (Hemilä et al, 2002(Hemilä et al, , 2004Meydani et al, 2004). The participants in the current study were healthy adults who exercised moderately and very few smoked.…”
Section: Discussionmentioning
confidence: 95%
“…Vitamin E supplementation in animal and human subjects resulted in increased lymphocyte proliferation, IL-2 production, and decreased production of the immunosuppressive factor PGE 2 (4,5). Furthermore, vitamin E supplementation was shown to reduce the risk of acquiring upper respiratory infection in the elderly (6) and influenza infection in old mice (7). Vitamin E exerts its effect on immune function in part by reducing macrophage PGE 2 production (4).…”
Section: ) Mo Et Al (2) Stimulated Purified Cd4mentioning
confidence: 99%